PSYCHOLOGICAL CHARACTERISTICS OF LEADING THE JUNIOR FOOTBALLERS' TEACHING - LEARNING PROCESS - D. BARBU; C. FORŢAN; D. STOICA (Editura Universitatii Transilvania din Brasov, 2020)
The coach is directly responsible for the good accomplishment of the process of transmitting the information, but especially for his result - preparing today's athletes to become members with full rights, but also with responsibilities in tomorrow's society. The paper highlights the priority aspects of the psychological peculiarities of the junior footballers' personality and their importance in gaining performance. The conclusions of the current research will make the coaches' teaching process as well as the athletes' learning more efficient